Between norms and interests: US and German democracy promotion in comparison - Wolff, Jonas; Spanger, Hans-Joachim; Karakas, Cemal (2012)
Abstract: Academic interest in democracy promotion notwithstanding, there is still little research that systematically compares different democracy promoters with a view to identifying the factors that explain variance in democracy promotion policies. The paper presents results of a research project that set out to contribute to filling this gap by analyzing the democracy promotion policies of two "donors" (USA, Germany) towards six "recipient" countries (Pakistan and Turkey, Bolivia and Ecuador, Russia and Belarus). It studies how "donor" states react to specific challenges that arise from "recipient" countries and that lead to conflicting objectives on the part of the democracy promoters. The paper asks how democracy promoters, across the twelve cases, deal with conflicting objectives and assesses the overall national patterns that characterize U.S. and German democracy promotion. With a view to both tasks, the paper offers causal explanations that are based on a theoretical framework that